1996
DOI: 10.1002/j.1460-2075.1996.tb00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Shc adaptor proteins are key transducers of mitogenic signaling mediated by the G protein-coupled thrombin receptor.

Abstract: The serine protease thrombin activates G protein signaling systems that lead to Ras activation and, in certain cells, proliferation. Whereas the steps leading to Ras activation by G protein‐coupled receptors are not well defined, the mechanisms of Ras activation by receptor tyrosine kinases have recently been elucidated biochemically and genetically. The present study was undertaken to determine whether common signaling components are used by these two distinct classes of receptors. Here we report that the ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 47 publications
(14 reference statements)
3
71
0
Order By: Relevance
“…In this report we present data suggesting that Shc also transduces thrombin and G 12 signals to gene expression and mitogenesis. Our results, in accordance with those of van Obberghen-Schilling's group (Chen et al, 1996), indicate that Shc is phosphorylated in response to activation of the thrombin receptor. This ®nding alone does not indicate that Shc functions in a proliferative pathway.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this report we present data suggesting that Shc also transduces thrombin and G 12 signals to gene expression and mitogenesis. Our results, in accordance with those of van Obberghen-Schilling's group (Chen et al, 1996), indicate that Shc is phosphorylated in response to activation of the thrombin receptor. This ®nding alone does not indicate that Shc functions in a proliferative pathway.…”
Section: Discussionsupporting
confidence: 93%
“…However, by microinjecting antibodies against phosphotyrosine or Shc, we have shown that tyrosine phosphorylation and Shc are indeed necessary for thrombin-stimulated mitogenesis in 1321N1 astrocytoma cells. These data extend those of a recent report demonstrating that a Shc mutant (Y317F), which acts as a dominant negative, inhibits thrombininduced focus formation in CCL39 cells (Chen et al, 1996). However, it should be noted that in that study the transforming e ect of thrombin was assessed in the presence of insulin, at concentrations su cient to activate the IGF-1 receptor which is expressed in ®broblasts and requires Shc for mitogenesis (Sasaoka et al, 1994).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The dbl proteins are themselves oncogenic, stimulate JNK activation and many show exchange factor activity towards the racrelated GTPases (Hart et al, 1994;Horii et al, 1994;Cerione and Zheng, 1996;Denhardt, 1996). Candidate molecules which could act upstream of these exchange factors include the src-like non-receptor tyrosine kinases, Pyk2 and the adaptor molecule shc (Dikic et al, 1996;Chen et al, 1996). Deletion of the src-like kinases Lyn, Syk, Btk and Csk abolishes muscarinic receptor activation of the MAP kinase cascade in avian Figure 4 Multiplexed assay of the e ects of ras and rac on proliferative responses to the Alpha 1B adrenergic receptor and the TrkC neurotrophin receptor.…”
Section: Alpha1bmentioning
confidence: 99%
“…Activation of the TSH-R, a G-protein coupled receptor, results in stimulation of adenylyl cyclase, elevation of cAMP levels and cAMP-dependent protein kinase (PKA) activation (Vassart and Dumont, 1992). Recent ®ndings suggest that Ras activation plays a role in mitogenic signal transduction induced by G-proteincoupled receptors (Alblas et al, 1993;Chen et al, 1996;Dikic et al, 1996;Sadoshima and Izumo, 1996). Indeed in thyroid cells, proliferation is dependent both on Ras as well as on PKA activation, since a dominant-interfering Ras mutant causes a signi®cant reduction of TSH-induced proliferation (Kupperman et al, 1993).…”
Section: Introductionmentioning
confidence: 99%